Ownership, control, and pyramids in Spanish commercial banks - Azofra, Valentín; Santamaría, Marcos (Journal of Banking & Finance, 2011)
Using the law and finance approach we analyze how the ultimate ownership and control structure influences the performance of Spanish commercial banks during the period 1996–2004. Our evidence shows that 96% of Spanish commercial banks have an ultimate controlling owner. Also, we observe that whenever there is a gap between the ultimate controlling owner’s cash flow and control rights, than the bigger the gap, the poorer the bank’s performance. We find that whenever there is no difference between the ultimate controlling owner’s cash flow and control rights, there is a non-monotonic relation between ownership concentration and the bank’s performance.